Niveles de inclusion de gramineas tropicales en el engorde de conejos Nueva Zelanda (Oryetulagus cuniculus) en la zona de Quevedo. - Mendoza Alcívar, Pedro Daniel (2013)
The research was carried out at the Experimental Farm "La Maria", owned by the State Technical University Quevedo (UTEQ), located at km 7 1/2 pathway Quevedo-Mocache; province of Los Rios, whose geographical location of 1 6 '23 "south latitude and 79 º 29' 22" W and a height of 73 meters. The investigation lasted 56 days. We evaluated different levels of flour in diets tropical grasses, the treatments were: T1 = 10% savoy, savoy T2 = 20%, T3 = 30% savoy, king grass T4 = 10% king grass T5 = 20%; king grass T6 = 30% 10% T7 = maralfalfa; maralfalfa T8 = 20%; maralfalfa T9 = T10 = 30% and diet (control). Conrjos 60 males were used 30 days of age with an average weight of 300 g. We used a factorial arrangement 3 (tropical grasses) x 3 (levels of inclusion) + 1 (Control), in a complete block design randomly (RCBD) with three replications, the experimental unit consisted of two animals. We applied the multiple range test of Tukey (P ≤ 0.05). The variables were: feed intake, weight gain, feed conversion and carcass yield. The profitability of the treatments were determined using the benefit - cost. Balanced consumption, live weight, weight gain, feed conversion and carcass yield, not affected by the effects and levels of tropical grasses (P> 0.05). The interaction (tropical grasses vs. inclusion levels) do not affect the growth performance of New Zealand rabbits (P> 0.05). The treatments were recorded the best performance with the T3 and T10 (27.51 and 27.08%, respectively). Keywords: Grasses, food, diets, rabbits.